Liability for Violation of Quarantine: Novelties of Administrative and Criminal Legislation - Стародубов, Сергій Вікторович; Стародубов, С. В.; Стародубов, Сергей Викторович; Starodubov, Serhii V.; Starodubov, Sergii; Владишевська, Вікторія Вікторівна; Владишевська, В. В.; Владышевская, Виктория Викторовна; Vladyshevska, Viktoriia V.; Пижова, Марина Олександрівна; Пижова, М. О.; Пижова, Марина Александровна; et al. (Los Hemisferios University, 2020)
Public legislation has long failed to meet such large-scale challenges as the SARS-CoV-2 pandemic. In emergencies, to protect the lives and health of the population, it is necessary to promptly make decisions on the legal regulation of public relations that have developed due to the spread of Covid-19. For this purpose, the state has created legal mechanisms that are designed to ensure compliance with the rule of law and which need the scientific-legal assessment. The objective of the work is to analyze the novelties of administrative and criminal legislation, which regulate the liability for violation of quarantine. The object of research is the norms of administrative and criminal law. The subject of the study is public relations that have developed as a result of the introduction of quarantine and which are governed by administrative and criminal law. To achieve this goal, the situation in foreign countries was firstly analyzed; general patterns were identified; alternative solutions were proposed, with a minimum restriction of human rights and freedoms. Then, the novelties of the national legislation were studied in more detail; additional specific problems were identified; and a more balanced legislative policy was proposed. As a result of the study, the current state of legal regulation in the areas of administrative and criminal law related to quarantine violations was analyzed; the liability for such offenses was characterized; some conclusions regarding the existing related problems were made and options for their solution were proposed, as well as propositions for modernization of legislation were made.

Публічне законодавство давно не відповідає таким масштабним викликам, як пандемія SARS-CoV-2. У надзвичайних ситуаціях для захисту життя та здоров’я населення необхідно оперативно приймати рішення щодо правового регулювання суспільних відносин, що склалися внаслідок поширення Covid-19. З цією метою держава створила правові механізми, які покликані забезпечити дотримання норм права і які потребують науково-правової оцінки. Метою роботи є аналіз новинок адміністративного та кримінального законодавства, які регулюють відповідальність за порушення карантину. Об’єктом дослідження є норми адміністративного та кримінального права. Предметом дослідження є зв’язки з громадськістю, які склалися в результаті запровадження карантину і які регулюються адміністративним та кримінальним законодавством. Для досягнення цієї мети спочатку було проаналізовано ситуацію в зарубіжних країнах; були виявлені загальні закономірності; було запропоновано альтернативні рішення з мінімальним обмеженням прав і свобод людини. Потім новели національного законодавства були вивчені більш детально; були виявлені додаткові конкретні проблеми; було запропоновано більш зважену законодавчу політику. В результаті дослідження проаналізовано сучасний стан правового регулювання у сферах адміністративного та кримінального права, пов’язаних із порушеннями карантину; характеризувалась відповідальність за такі правопорушення; зроблено деякі висновки щодо існуючих супутніх проблем та запропоновано варіанти їх вирішення, а також пропозиції щодо модернізації законодавства.

Государственное законодательство давно не способно противостоять таким масштабным вызовам, как пандемия SARS-CoV-2. В чрезвычайных ситуациях для защиты жизни и здоровья населения необходимо оперативно принимать решения по правовому регулированию общественных отношений, сложившихся из-за распространения Covid-19. Для этого в государстве созданы правовые механизмы, призванные обеспечить соблюдение законности и нуждающиеся в научно-правовой оценке. Цель работы - проанализировать новинки административного и уголовного законодательства, регулирующие ответственность за нарушение карантина. Объект исследования - нормы административного и уголовного права. Предмет исследования - связи с общественностью, которые сложились в результате введения карантина и регулируются административным и уголовным законодательством. Для достижения этой цели сначала была проанализирована ситуация в зарубежных странах; были выявлены общие закономерности; Были предложены альтернативные решения с минимальным ограничением прав и свобод человека. Затем более подробно были изучены новинки национального законодательства; выявлены дополнительные специфические проблемы; предложена более взвешенная законодательная политика. В результате исследования было проанализировано текущее состояние правового регулирования в сфере административного и уголовного права, связанного с карантинными нарушениями; охарактеризована ответственность за такие правонарушения; сделаны выводы относительно существующих проблем и предложены варианты их решения, а также внесены предложения по модернизации законодательства.
Starodubov S. Liability for Violation of Quarantine: Novelties of Administrative and Criminal Legislation / S. Starodubov, V. Vladyshevska, M. Pyzhova // Ius Humani. Law Journal. – V. 9(2). – Los Hemisferios University, 2020. – P. 137-158.
Keywords: Coronavirus; Quarantine; Offense; Liability; Fine; коронавірус; карантин; правопорушення; відповідальність; штраф; коронавирус; карантин; правонарушение; ответственность; штраф; Research Subject Categories::LAW/JURISPRUDENCE